Ethnomathematics-Collaborative Augmented Reality: An Innovative Framework to Enhance Problem-Solving Skills in Elementary Geometry - I Nyoman Jampel; I Gede Wahyu Suwela Antara (Jurnal Ilmiah Sekolah Dasar, 2024)
This study addresses the urgent need to develop problem-solving skills among elementary school students as a fundamental basis for effective learning processes. The research aims to analyze the effectiveness of a geometry framework based on ethnomathematics-collaborative augmented reality in enhancing students' problem-solving abilities. This experimental research employs a quantitative approach with a one-group pre-test post-test design. The study involved 30 fourth-grade elementary school students as subjects. The effectiveness of the framework was measured using pre-test and post-test methods. Data analysis was conducted using descriptive and inferential statistics, with the Paired Sample T-Test applied to test the hypothesis, utilizing IBM SPSS Statistics for Windows version 21.0. The results indicated a significant difference in students' problem-solving abilities before and after the implementation of the geometry framework. The post-test results showed a notable improvement in students' problem-solving skills compared to the pre-test. The application of the ethnomathematics-collaborative augmented reality framework proved effective in providing contextual, collaborative, and technology-based learning experiences, which significantly enhanced students' problem-solving capabilities. Therefore, this framework offers a relevant innovation in geometry learning for elementary education, promoting the integration of local cultural values into the learning process and supporting students’ cognitive development through problem-solving tasks.